A rare case of co-existing Treacher-Collins and Down syndrome. (December 2016) - Thoukididou, Sarah; Ubayasiri, Kishan; Ramsay, Margaret; Wake, Suzanne; Davies, Patrick; Daniel, Mat
Abstract: Both Treacher-Collins (TCS) and Down syndrome cause structural and functional airway abnormalities. We present the case of a neonate with both syndromes who required tracheostomy in the first hour of life due to severe upper airway obstruction. The co-occurrence of both syndromes is rare, and presents unique challenges in securing the airway in the perinatal period.